Intolerance of Uncertainty Moderates the Association Between Potentially Morally Injurious Events and Suicide Ideation and Behavior Among Combat Veterans. Issue 3 (5th February 2019) - Zerach, Gadi; Levi‐Belz, Yossi
Abstract: Exposure to potentially morally injurious events (PMIEs) among combat veterans has been acknowledged as significant stressful combat events that may lead to mental health problems, including self‐injurious thoughts and behavior (SITB). However, few studies have examined the risk and protective factors that can explain the conditions in which PMIEs may contribute to the development and maintenance of SITB. In the current study, we aimed to examine the association between PMIEs and SITB among combat veterans and explore the moderating roles of intolerance of uncertainty (IU) in this association. A volunteer sample of 191 Israeli combat veterans was recruited during 2017. Participants completed validated self‐report questionnaires in a cross‐sectional study. Results indicated that two separate measures of PMIEs, the Perceived Perpetration by Oneself and Others subscale of the Moral Injury Events Scale (MIES) and the Causes subscale of the Moral Injury Questionnaire (MIQ–Causes), were positively associated with higher levels of SITB. Moreover, beyond the contributions of reserve duty, posttraumatic stress symptoms, and depressive symptoms, MIQ–Causes scores significantly predicted current SITB. Importantly, under low and average levels of inhibitory IU, significant positive effects were revealed for the MIQ–Causes on current SITB, R ² = .34. Although veterans exposed to PMIEs are more prone to SITB, even years after their release from military service, their IU may temper the link between experiences of PMIEs and SITB. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) La Intolerancia a la Incertidumbre Modera la Asociación entre los Eventos Potencialmente Dañinos Moralmente, la Ideación, y las Conductas Suicidas entre los Veteranos Combatientes DAÑO MORAL Y SUICIDIO La exposición a los eventos potencialmente dañinos moralmente (PMIEs en sus siglas en inglés) entre los veteranos combatientes ha sido reconocidos como aquellos eventos de combate significativamente estresantes que pueden conllevar problemas de salud mental, incluyendo los pensamientos y las conductas autolesivos (SITB en su sigla en inglés). Sin embargo, solo unos pocos estudios han examinado los factores de riesgo y protectores que pueden explicar las condiciones en las que los PMIES podrían contribuir al desarrollo y mantención de los SITB. En el presente estudio, se busca examinar la asociación entre los PMIEs y los SITB entre los veteranos combatientes y explorar los roles moderadores de intolerancia a la incertidumbre (IU en su sigla en inglés) en esta asociación. Se reclutó durante el 2017 una muestra voluntaria de 191 veteranos combatientes israelíes. Los participantes completaron cuestionarios validados de auto‐reporte de un estudio trasversal. Los resultados indicaron que las dos medidas distintas de los PMIEs, la subescala de Perpetración Percibida por Uno Mismo y Otros de la Escala de Eventos Dañinos Morales (MIES en sus siglas en inglés) y la subescala Causas del Cuestionario de Daño Moral (MIQ en sus siglas en inglés‐Causas), se asociaron positivamente con niveles más altos de los SITB. Además, más allá de las contribuciones del servicio de reserva, los síntomas de estrés postraumáticos, y los síntomas depresivos, los puntajes de las MIQ‐Causas predijeron significativamente los SITB actuales. De forma importante, con niveles bajos y medios de la inhibida IU, los efectos positivos significativos fueron revelados para las MIQ‐Causas en los SITB actuales, R 2 = .34. Aunque los veteranos expuestos a los PMIEs fueron más propensos a los SITB, incluso años después del término de su servicio militar, su IU podría mitigar la conexión entre las experiencias de los PMIEs y los SITB. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Intolerance of Uncertainty Moderates the Association between Potentially Morally Injurious Events, Suicide Ideation and Behavior among Combat Veterans Traditional Chinese 標題: 退役戰鬥軍人對不確定性的難耐, 對於潛在會導致道德創傷的事件經歷、自殺意念和行為之間的關連有調節作用 撮要: 戰鬥軍人的潛在會導致道德創傷的事件經歷(PMIEs), 在過往研究被視為顯著高壓戰鬥事件, 有可能導致心理問題, 包括產生自殘想法和行為(SITB)。可是, 只有少量研究檢視能解釋PMIEs有可能導致SITB發展和維持的風險和保護因素。本研究旨在檢視戰鬥軍人中PMIEs 與 SITB的關連, 並探索對不確定性的難耐(IU)在關連中的調節效應。我們於2017年招募了191名以色列退役戰鬥軍人自願參與作為樣本。在橫斷研究中, 樣本完成已驗證的自評問卷。結果反映, PMIEs的兩種測量法跟有較高水平的SITB有正向關連:道德創傷事件量表(MIES)中對自己和他人犯罪的感知子量表, 及道德創傷問卷中的起因子量表(MIQ–Causes)。再者, 除了預備役、創傷後壓力症狀和抑鬱症狀能預測當前的SITB外, MIQ–Causes分數亦能顯著地預測當前的SITB。重要的一點是, 當抑制性的IU處於低或中等水平時, MIQ–Causes對當前的SITB具有顯著的正向效應(R 2 = .34)。雖然有PMIEs的退役軍人即使在退役多年後仍較傾向有SITB, 他們的IU可能會干預PMIEs與SITB的關連。 Simplified Chinese 撮要: 战斗军人的潜在会导致道德创伤的事件经历(PMIEs), 在过往研究被视为显著高压战斗事件, 有可能导致心理问题, 包括产生自残想法和行为(SITB)。可是, 只有少量研究检视能解释PMIEs有可能导致SITB发展和维持的风险和保护因素。本研究旨在检视战斗军人中PMIEs 与 SITB的关连, 并探索对不确定性的难耐(IU)在关连中的调节效应。我们于2017年招募了191名以色列退役战斗军人自愿参与作为样本。在横断研究中, 样本完成已验证的自评问卷。结果反映, PMIEs的两种测量法跟有较高水平的SITB有正向关连:道德创伤事件量表(MIES)中对自己和他人犯罪的感知子量表, 及道德创伤问卷中的起因子量表(MIQ–Causes)。再者, 除了预备役、创伤后压力症状和抑郁症状能预测当前的SITB外, MIQ–Causes分数亦能显著地预测当前的SITB。重要的一点是, 当抑制性的IU处于低或中等水平时, MIQ–Causes对当前的SITB具有显著的正向效應(R 2 = .34)。雖然有PMIEs的退役軍人即使在退役多年後仍較傾向有SITB, 他們的IU可能會干預PMIEs與SITB的關連。